Schnitzler Syndrome: A Dramatic Response to Anakinra. Issue 2 (June 2016) - Gouveia, Ana; Micaelo, Manuela; Pierdomenico, Francesca; Freitas, João
Abstract Schnitzler syndrome is a rare acquired systemic disease with a chronic evolution and difficult treatment. We report a 50-year-old woman with Schnitzler syndrome for 10 years, with major impact on her quality of life and refractory to conventional therapies. The patient was started on anakinra, an IL-1 receptor antagonist, with a rapid and sustained remission of the syndrome manifestations.